Synthesis and characterization of tetrafluorophenyl phosphonic acid functionalized polyacrylates as potential proton conducting materials in fuel cells. Issue 3 (5th November 2022) - Alter, Christian; Weitkamp, Robin F.; Hoge, Berthold
Abstract: Novel acrylate polymers functionalized with tetrafluorophenyl phosphonic acid groups were prepared by free radical polymerization of phosphonic ester acrylate monomers. Liberation of the free acid functions was realized by ester cleavage with Me3 SiBr and the subsequent hydrolysis with methanol. The obtained polymers were analyzed by NMR and IR spectroscopy. The ion exchange capacity of the phosphonic acid functionalized methacrylate polymer was determined to 2.8 mmol/g by titration with 0.1 M NaOH. The proton conductivity under anhydrous conditions was determined to 6.84 × 10 −6 Scm −1 at 120°C by electrochemical impedance spectroscopy. Abstract : Fluorinated phosphonic acids are high‐performance materials for proton conduction applications. The bonding of phosphonic acids to a polymer backbone for application as electrolytes in polymer electrolyte membrane fuel cells is of broad interest. Here, we present acrylate‐based tetrafluorophenylene phosphonic acid polymers with high proton conductivity under anhydrous conditions and elevated temperatures.